(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
Porcini mushrooms (Boletus sect. Boletus) have both economic and ecological importance. During this study, a specimen of the phenotypically complex species Boletus himalayensis was analyzed morphologically and molecular genetically. This bolete speciesis characterized bya combination of porcini features: whitish pileus margin and context, pore surface and overall basidiomata having a whitish look before maturity and ithas a considerably longer stipe compared to the pileus diameter when immature, with whitish reticulation extending longitudinally towards base. The whitish context and the white to white yellowish pore surface both do not change color upon bruising. Although the specimen exhibited a long stipe and a small non−cracked pileus as compared to other collections of Boletus himalayensis, molecular genetic analysis revealed that it belongs to this species. Bangladesh J. Plant Taxon. 30(1): 99-106, 2023 (June)